National Trends of Surgical Treatment for Intertrochanteric Fractures in Korea - Lee, Young-Kyun (The Korean Academy of Medical Sciences, 2013)
Intramedullary nailing has been reported to have better outcome compared with traditional plate fixation in surgical treatment of intertrochanteric fractures. We evaluated the trends of surgical treatment of intertrochanteric fracture in Korea. Data of patients with intertrochanteric fractures, who were operated between the years of 2006 and 2011, was obtained from the Health Insurance Review and Assessment Service. The ratio of intramedullary nailing increased from 27.9% in 2006 to 64.3% in 2011 (P < 0.001), while the ratio of plate fixation decreased. During recent 5 yr, the utilization of intramedullary nailing doubled in clinical practice of intertrochanteric fractures in Korea.